2007
DOI: 10.1073/pnas.0611721104
|View full text |Cite
|
Sign up to set email alerts
|

An in vivo correlate of exercise-induced neurogenesis in the adult dentate gyrus

Abstract: With continued debate over the functional significance of adult neurogenesis, identifying an in vivo correlate of neurogenesis has become an important goal. Here we rely on the coupling between neurogenesis and angiogenesis and test whether MRI measurements of cerebral blood volume (CBV) provide an imaging correlate of neurogenesis. First, we used an MRI approach to generate CBV maps over time in the hippocampal formation of exercising mice. Among all hippocampal subregions, exercise was found to have a primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

64
952
3
23

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 1,189 publications
(1,042 citation statements)
references
References 57 publications
64
952
3
23
Order By: Relevance
“…Research pertaining to the underlying mechanisms has revealed significant central physiological and structural changes resulting from exercise. In particular, in the hippocampus, a brain region important for learning and memory, running increases neurotrophin gene expression (8,9), vascularization (10,11), dendritic spine density (12,13), and synaptic plasticity (6,9). These exercise-induced changes are associated with a robust increase in dentate gyrus neurogenesis in young rodents as well as a reversal of the agingrelated decline in cell genesis (6,7,10,14).…”
mentioning
confidence: 96%
“…Research pertaining to the underlying mechanisms has revealed significant central physiological and structural changes resulting from exercise. In particular, in the hippocampus, a brain region important for learning and memory, running increases neurotrophin gene expression (8,9), vascularization (10,11), dendritic spine density (12,13), and synaptic plasticity (6,9). These exercise-induced changes are associated with a robust increase in dentate gyrus neurogenesis in young rodents as well as a reversal of the agingrelated decline in cell genesis (6,7,10,14).…”
mentioning
confidence: 96%
“…Higher physical activity level seems to be able to increase gray and white matter volume in the prefrontal cortex (Colcombe et al, 2006) and is associated with greater sparing of prefrontal and temporal brain regions (Erickson et al, 2010). Moreover, exercise training increases cerebral blood volume (Burdette et al, 2010) and perfusion of the hippocampus (Pereira et al, 2007), one of the most important organ in the control of food intake. If these anatomical changes correspond to better cognitive function is, however, not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Major depressive disorder (MDD) has been associated with reductions in hippocampal and amygdalar volume that are thought to reflect dendritic atrophy occurring in the context of excitotoxicity, decreased neurogenesis, and impaired neurotrophic function (Koolschijn et al, 2009;Pereira et al, 2007;Petrik et al, 2012;Savitz and Drevets, 2009;Stockmeier et al, 2004). At least a subgroup of individuals with MDD also display putative signs of inflammation such as elevated circulating concentrations of C-reactive protein (CRP), interleukin-6 (IL-6), and interleukin-1b (IL-1b) (Dowlati et al, 2010;Howren et al, 2009).…”
Section: Introductionmentioning
confidence: 99%